Validation of a heat stress index and hydration of workers in tropical Australia - Miller, Veronica Susan (Curtin University, 2007)
In many parts of Australia the climate is such that people are working long hours in the heat. Consequences of excessive environmental heat stress range from reduction in safety due to impairment of concentration, to heat illness, which in extreme cases can be fatal. A critical factor in tolerance of workers to environmental heat stress is their level of hydration. Maximising productivity without compromising the health and safety of the work force requires quantification of the degree of stress posed by the thermal environment. For this purpose a number of heat stress indices have been developed. A recently introduced index is the Thermal Work Limit (TWL), which has been widely adopted and implemented in the underground mining industry in Australia. The field use of TWL and protocols in the mining industry with resultant reduction in heat illness and lost production is a practical endorsement of the index, and its validity under controlled conditions has been confirmed by a preliminary study. The further work needed to complete this validation forms part of this thesis. TWL was found to reliably predict the limiting workload in the controlled environment, reinforcing the validity of the algorithm and its application in the workplace. To date TWL has largely been used in the underground environment, however as the algorithm is equally applicable to the above ground environment where radiant heat forms a significant component of the thermal load, field studies were carried out at mining installations in the Pilbara region of Western Australia to evaluate this application of the index. The current industry standard index of heat stress is the Wet bulb Globe Temperature (WBGT).The shortcomings of this index are widely acknowledged and in practice it is frequently ignored as it is seen to be unnecessarily conservative in many situations. The sensitivity of TWL to the cooling effect of air movement implied that TWL would be more relevant than WBGT as a predictor of the impact of environmental heat stress in outdoor work environments and this was supported by the results. On the strength of this, recommended management protocols linked to TWL similar to those already in place in many underground workplaces, were developed for the management of thermal risk in outdoor work environments. Maintaining adequate hydration is the single most important strategy to counteract the effects of thermal stress. No heat stress index can protect workers from the combined effects of dehydration and thermal stress. To document the hydration status of the outdoor workforce in the Pilbara, the hydration level of groups of workers was assessed from the specific gravity of their urine. To further evaluate whether the fluid replacement behaviour of the workers is adequate to replace fluids lost in sweat, a fluid balance study was carried out to quantify average fluid intakes and sweat fluid losses. The majority of workers were found to be inadequately hydrated at the start of the shift and their fluid intakes were in general well below the requirements to replace sweat losses - let alone improve hydration. Recommendations for fluid intakes based on documented rates of sweat loss are included in the thesis. Based on the findings of this study workable management strategies have been recommended to minimise the risk to outdoor workers in thermally stressful environments.